Satan’s Temptation of Jesus in the Gospels: A Critical study - Shanti , Emad Al-Din (Jordan Journal of Islamic Studies, 2023)
The research examines the Satan’s temptation of Jesus in the Gospels by analyzing the places where this story is mentioned in the three Gospels: Matthew, Luke, and Mark. It also studies this phenomenon in some ancient religions and compares it with what is mentioned in the Gospels. The research then delves into the incident within the Gospels, comparing them with each other, highlighting their differences, and drawing parallels with what is found in ancient pagan religions. Additionally, it presents a critique of this story and demonstrates its invalidity through rational analysis. Lastly, it discusses the Islamic perspective on this matter.